Effect of Heavy Mass Ion (Gold) and Light Mass Ion (Boron) Irradiation on Microstructure of Tungsten. (December 2019) - Sharma, Prashant; Maya, Padivattathumana; Akkireddy, Satyaprasad; Raole, Prakash M.; Tyagi, Anil K.; Attri, Asha; Kulriya, Pawan K.; Bajpai, Parmendra K.; Mishra, Sudhir; Patel, Shiv P.; Trivedi, Tarkeshwar; Khan, K. B.; et al.
Abstract: The difference in the defect structures produced by different ion masses in a tungsten lattice is investigated using 80 MeV Au 7+ ions and 10 MeV B 3+ ions. The details of the defects produced by ions in recrystallized tungsten foil samples are studied using transmission electron microscopy. Dislocations of type b = 1/2[111] and [001] were observed in the analysis. While highly energetic gold ion produced small clusters of defects with very few dislocation lines, boron has produced large and sparse clusters with numerous dislocation lines. The difference in the defect structures could be due to the difference in separation between primary knock-on atoms produced by gold and boron ions.